The Relationship of Sustainable Buying Behavior Dimensions Among the Gen Z: Modeling the Impact of Psychological Factors - Eunice Mareth Querol Areola, Phd HSG; Irvin Perono; Joan Camille Ilagan (Journal of Sustainable Community Development (JSCD), 2022)
Sustainable consumption has continuously become a trend in the behavior of consumers over the recent decades due to drastic changes in technological advancement, economic development, and population growth on a global scale. This research aimed to establish the relationship among the dimensions of sustainable purchase behavior of the Gen Z living in Metro Manila, Philippines. Multiple regression analysis was used to establish the psychological factors of Generation Z's overall sustainable purchase behavior. Findings revealed that the Perceived Knowledge About Sustainability Issues (PKSI), Attitude Towards Sustainable Purchasing Behavior (ATS), Sustainable Purchase Behavior (SPB), Spirituality (SP), Perceived Consumer Effectiveness (PCE), Drive for Environmental Responsibility (DER), and Perceived Marketplace Influence (PMI) dimensions were positively correlated among each dimensions.